2023
DOI: 10.15671/hjbc.1256836
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Siderophore Production and Associated Heavy Metal Accumulation Potential of Brevibacillus laterosporus 301/İK3-2

Abstract: Siderophores are secondary metabolites released into the environment by various microorganisms, fungi, and plants to chelate iron from the surrounding environment. It is known that siderophores bind to other metals besides iron. Today, heavy metals, which are released as an undesirable result of industrial development, accumulate at high rates and pose a significant threat to biological living things. In this sense, remediation of heavy metal-contaminated sites is an urgent requirement. Siderophores are promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Pseudomonas species are wellknown for their metabolic diversity and ability to thrive in various environmental conditions while Streptomyces species, known for their proli c production of antibiotics, also play a crucial role in soil health and HM tolerance. Özdemir, Aydın [39] has demonstrated that Pseudomonas can produce siderophores, which are iron-chelating compounds that also bind other HM, reducing their toxicity and facilitating their uptake and sequestration. Lemare, Puja [40] studied Pseudomonas species can biotransform HM into less toxic forms through redox reactions, thereby mitigating metal-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas species are wellknown for their metabolic diversity and ability to thrive in various environmental conditions while Streptomyces species, known for their proli c production of antibiotics, also play a crucial role in soil health and HM tolerance. Özdemir, Aydın [39] has demonstrated that Pseudomonas can produce siderophores, which are iron-chelating compounds that also bind other HM, reducing their toxicity and facilitating their uptake and sequestration. Lemare, Puja [40] studied Pseudomonas species can biotransform HM into less toxic forms through redox reactions, thereby mitigating metal-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%